Preparation and Antimicrobial Activity of 2-Phenyl-3-Aryl Sulphonamido Indoles and N’-Benzothiazol-2-yl-Thioactyl-N2-Arylsuphonyl Hydrazines - Trivedi, Bhavin; Shah, V.H. (Asian Journal of Chemistry, 2010)
A series of 2-phenyl-3-arylsulphonamido indoles (3a-1) and N1-benzothiazol-2-yl-thioacetyl-N2-aryl sulphonyl hydrazines (5a-1) have been prepared and screened for their antibacterial and antifungal activity. Most of them exhibited moderate to good activity. The structures of the compounds have been elucidated by IR and PMR and mass spectral data.